ANALISIS MODAL KERJA DAN PROFITABILITAS PADA PT HANJAYA MANDALA SAMPOERNA TBK PERIODE 2020–2024 - Oktavia Gundisalvus Dua Raha; Andreas Rengga; Cicilia Ayu Wulandari Nuwa (Universitas Nusa Nipa Maumere, 2026)
The background of this study was the fluctuation in net profit and the changes in current assets and current liabilities, which indicated an imbalance in the management of working capital at PT Hanjaya Mandala Sampoerna Tbk during the 2020–2024 period). This study aimed to analyze the company's working capital and profitability, which were measured using the Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) ratios. This study employed a descriptive research design with a quantitative approach.. The data consisted of the company's financial statements for the 2020–2024 period, which were obtained from the Indonesia Stock Exchange and the company's official website.. The results showed that the company's working capital remained positive but tended to decline, indicating a less favorable condition . The company's profitability was generally categorized as good, although the Gross Profit Margin was still considered less satisfactory.